PENGARUH MOTIVASI BELAJAR DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI SISWA KELAS XI IPS DI SMA NEGERI 1 BATANG CENAKU - Ayuni Sundari; Suarman Suarman; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the influence of learning motivation and learning outcomes towards school environment students in SMA Negeri 1 batang cenaku. The population in this research is the whole grade XI IPS in SMA Negeri 1 batang cenaku as much as 56 students and on research using sample census technique where all the population sample was made namely 56 students. Data were collected using a questionnaire about motivation and learning environment of schools that distributed to respondents. Data analysis data analysis using linear multiple regression test. Based on the results of the research of the influence of motivation and learning environment of the school towards the learning outcomes grade XI IPS on economic subjects in SMA Negeri 1 stalk Rantau Langsat is 0.479 or 47.9% 52.1% while the rest is influenced by other factors are not examined in this study such as physical factors, fatigue, family circumstances, and the public.Key Wods : Learning motivation, school environment, learning outcomes.